Three Rival Versions of a Correlation Between Solitude and Communitiveness in a Monoseological Discourse - Piotr Domeracki (Nicolaus Copernicus University in Toruń, 2020)
As the title states, this article focuses on a controversial topic: the lack of satisfactory solutions to the problem of the limits of the phenomena of solitude and communitiveness. It is based on the idea that monoseological discourse is intrinsic to this discourse. The term 'monoseology' is derived from two combined ancient Greek words: 'monosé', which means 'solitude'; and 'logos', translated etymologically as 'a rational, critical thinking', and more specifically as 'a science', 'a theory'. Hence, monoseology, in its wider meaning, is used to designate all sciences interested in analysing and conducting systematic research on solitude; in a narrower sense, the term 'monoseology' means simply the philosophy of solitude. It is quite commonly agreed that solitude in itself only consists of negative aspects, but communitiveness on the contrary has only positive ones. Therefore, solitude deserves clear and firm criticism, while communitiveness is assessed in a univocally positive way. This, in turn, translates to an unquestioning preference for ideas, feelings, motives and acts which are of community character and use. On the other hand, loneliness is recognised as a reason for our pain, suffering, fears, sadness and horrible despair. The result is the assumption that our key ambition, need and aim is to avoid and prevent each form of loneliness in our private and social life, at all costs. However, this causes many further problems - not only theoretical, but unfortunately also practical - which some researchers and ordinary people must face. This kind of unilateral and unambiguous interpretation of both solitude and communitiveness is called in the article 'monolectical'. In addition, it is shown here that the 'monolectics' of communitiveness or solitude is insufficient to provide an objective and complete picture of the two. In consequence, it is argued that monoseological discourse can succeed and develop itself only by turning to the dialectical method of explaining. The fundamental thesis and belief of this approach, expressed based on the dialectic of solitude and communitiveness, is that solitude and communitiveness are not at all isolated but strongly complementary. A practical conclusion arises from this statement: that each of us should intertwine in his or her life some periods of communitiveness and then some episodes of solitude.